2013
DOI: 10.1159/000351432
|View full text |Cite
|
Sign up to set email alerts
|

Do High Levels of n-3 Polyunsaturated Fatty Acids in Cell Membranes Increase the Risk of Postoperative Atrial Fibrillation?

Abstract: Objectives: Postoperative atrial fibrillation (POAF) has been associated with an inflammatory response to the surgical procedure. n-3 long-chain polyunsaturated fatty acids (LC-PUFA) have been proposed for the prevention of POAF. We investigated the relationship between the plasma concentration of inflammatory mediators, levels of n-3 LC-PUFA in red blood cell (RBC) membrane lipids, and the risk of POAF after coronary artery bypass grafting (CABG). Methods: A total of 125 patients who underwent CABG were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…A Danish cohort study supports the observation from the Japanese study; the Danish cohort study reported a monotonic, negative, dose-response trend for DHA, EPA and DPA and atrial fibrillation [45]. In fact, higher levels of DHA and total LCω-3PUFA in RBC membranes, measured immediately prior to coronary artery bypass grafting and on postoperative day 3, were linearly associated with an increased risk of postoperative AF [46]. These findings contradict the widely held view that LCω-3PUFA exposure decreases risk of ventricular arrhythmias, as well as the prevention and treatment of AF [47].…”
Section: Introductionsupporting
confidence: 58%
“…A Danish cohort study supports the observation from the Japanese study; the Danish cohort study reported a monotonic, negative, dose-response trend for DHA, EPA and DPA and atrial fibrillation [45]. In fact, higher levels of DHA and total LCω-3PUFA in RBC membranes, measured immediately prior to coronary artery bypass grafting and on postoperative day 3, were linearly associated with an increased risk of postoperative AF [46]. These findings contradict the widely held view that LCω-3PUFA exposure decreases risk of ventricular arrhythmias, as well as the prevention and treatment of AF [47].…”
Section: Introductionsupporting
confidence: 58%
“…The development of atrial fibrillation (AF) after cardiac surgery has been associated with poor cardiac outcome . Several variables, including inflammatory mediators, age, or left ventricular (LV) function, have been shown to be involved in the development of post‐operative atrial fibrillation (POAF) . Sympathetic system activation may also be associated with POAF development, which has been reported to be reduced by the use of beta‐blockers before the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In this open-label, prospective, randomized clinical trial, the use of PUFAs was associated with a 65% reduction of postoperative AF. Subsequently, multiple smaller trials evaluated the role of perioperative supplementation with PUFAs and the effect of this on postoperative AF, but the results were far from convincing [5,8,9,10]. Recently, Mozaffarian et al [12] studied 1,516 patients scheduled for cardiac surgery, the largest trial to date.…”
mentioning
confidence: 99%
“…In a recent issue of Cardiology , Bjorgvinsdottir et al [5 ]have assessed the effects of PUFAs on postoperative AF. In this elegant study, the investigators quantified PUFAs in the cell membrane of red blood cells (RBC) and also quantified certain surrogate inflammatory markers (IL-1β, IL-6, IL-8, IL-12, IL-18, IF-γ, TNF-α, TNF-β, MIP-1α, IL-10, TGF-β and hs-CRP).…”
mentioning
confidence: 99%
See 1 more Smart Citation